Frecuencia y susceptibilidad antibiótica de enterobacterias de urocultivos de los moradores de la nueva ciudad de Belén Varillalito. Iquitos-Perú - Ruíz Vásquez, Viviam Verónica (2024)
Antibiotic resistance is an increasingly complex public health problem and is considered a real threat worldwide. The objective was to evaluate the frequency and antibiotic susceptibility of enterobacteriaceae in urine cultures from residents of the new town of Belén Varillalito. Three hundred urine samples were collected from residents over 18 years of age. Enterobacteriaceae were isolated and identified by conventional methods based on phenotypic and metabolic characteristics of bacterial growth on culture media. For antibiotic susceptibility, the Kirby-Bauer method (Agar Diffusion) was applied where 8 antibiotics were used; Amoxicillin/Clavulanic Acid, Ampicillin, Amikacin, Gentamicin, Ciprofloxacin, Cephalexin, Nitrofurantoin and Clindamycin. Of the 300 urine samples collected, 131 samples were positive for Enterobacteriaceae, 56 strains belonging to Klebsiella sp (43%), 44 to Escherichia coli (34%) and 31 to Proteus sp (24%). Statistically, the antibiotics with the highest frequency of sensitivity in the 3 species of Enterobacteriaceae were; Gentamicin (98%) and Ciprofloxacin (96%), the antibiotic with the highest intermediate frequency in the Klebsiella sp and Escherichia coli genera was; Nitrofurantoin (90%) and the antibiotic to which the Enterobacteriaceae presented the highest frequency of resistance was; Clindamycin (98%).